Integrating Reptilian Herpesviruses into the Family Herpesviridae - McGeoch, Duncan J. (American Society for Microbiology, 2005)
The phylogeny of reptilian herpesviruses (HVs) relative to mammalian and avian HVs was investigated by using available gene sequences and by alignment of encoded amino acid sequences and derivation of trees by maximum-likelihood and Bayesian methods. Phylogenetic loci were obtained for green turtle HV (GTHV) primarily on the basis of DNA polymerase (POL) and DNA binding protein sequences, and for lung-eye-trachea disease-associated HV (LETV) primarily from its glycoprotein B sequence; both have nodes on the branch leading to recognized species in the Alphaherpesvirinae subfamily and should be regarded as new members of that subfamily. A similar but less well defined locus was obtained for an iguanid HV based on a partial POL sequence. On the basis of short POL sequences (around 60 amino acid residues), it appeared likely that GTHV and LETV belong to a private clade and that three HVs of gerrhosaurs (plated lizards) are associated with the iguanid HV. Based on phylogenetic branching patterns for mammalian HV lineages that mirror those of host lineages, we estimated a date for the HV tree's root of around 400 million years ago. Estimated dates for branching events in the development of reptilian, avian, and mammalian Alphaherpesvirinae lineages could plausibly be accounted for in part but not completely by ancient coevolution of these virus lines with reptilian lineages and with the development of birds and mammals from reptilian progenitors.